Effect Of Chlorohexidine Mouth Wash and Silver Nanoparticles on Bacterial Count in Maxillary Cleft Patients. A Cross-Sectional Study - Mohammed Hassan, Ehab A Atito, Wesam E Badr , Farid Abdel Karim Hamam, Adel Fawzy Abd El Hakim, Mohamed kassem Ahmed Radwan, Ahmed Fathey Elhagali, Mostafa S.Swedan (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Aims: To evaluate the effect of chlorhexidine silver nanoparticles on bacterial count in maxillary cleft patients. Methodology: Ten patients with cleft palate received three different care modalities; (M1) (Control) Obturator lined by soft liner, (M2) Obturator lined by soft liner and used 0.125% chlorhexidine HCl mouth wash two times daily, while in (M3) Obturator lined by soft liner containing 0.1% silver nano particles (Ag-Nps).